Vulpinic acid, a lichen metabolite, emerges as a potential drug candidate in the therapy of oxidative stress–related diseases, such as atherosclerosis. (June 2019) - Sahin, E; Dabagoglu Psav, S; Avan, I; Candan, M; Sahinturk, V; Koparal, AT
Vulpinic acid, a lichen compound, has been shown to have many beneficial effects and its medicinal value increases day by day. As in atherosclerosis, endothelial damage is the basis of many diseases. The aim of this study is to investigate the effects of vulpinic acid against oxidative stress damage induced by hydrogen peroxide (H2 O2 ) in endothelial cells. In order to find the IC50 of H2 O2 and the protective dose of vulpinic acid, methyl thiazolyldiphenyl tetrazolium bromide (MTT) assays were performed. The amount of reactive oxygen species (ROS) induced by H2 O2 and the protective effects of vulpinic acid against ROS were examined by fluorometric DCF-DA kit. The effects of H2 O2 and vulpinic acid on actin filaments were determined by tetramethyl rhodamine (TRITC)-phalloidin fluorescence staining. Expression of Tie2 proteins was immunocytochemically analyzed in H2 O2 - and vulpinic acid-treated cells. After 24 h, the IC50 was found to be 215 μM in HUVECs treated with H2 O2 . The most effective dose of vulpinic acid against H2 O2 -associated damage was found to be 15 μM. Vulpinic acid pretreatment was shown to reduce H2 O2 -induced ROS production significantly ( p < 0.05). It was shown that 215 μM of H2 O2 caused actin fragmentation, cell shrinkage, and decrease in actin florescence intensity while vulpinic acid protected the cells from these damages. It was found that Tie2 immunoreactivity was decreased in H2 O2 -treated groups and vulpinic acid pretreatment reduced the expression of this protein. In conclusion, vulpinic acid decreases H2 O2 -induced oxidative stress and oxidative stress–related damages in HUVECs. It may be drug candidate in the therapy of atherosclerosis.